Dual Burden of Malnutrition Among Adolescents With Hunger Aged 12–15 Years in 41 Countries: Findings From the Global School-Based Student Health Survey - Liu, Huaqing; Zhang, Min; Fu, Peipei; Chen, Yan; Zhou, Chengchao (Frontiers in Medicine, 2022)
Background: Hunger is a pandemic among adolescents, resulting in both underweight and obesity, and posing a substantial health challenge. Objective: To estimate the dual burden of malnutrition among adolescents with hunger. Design: Data were from the Global school-based Student Health Survey (GSHS). In total, data from 26,986 adolescents with hunger across 5 regions and 41 countries between 2010 and 2015 were analyzed in this study. Weighted prevalence and mean estimates of underweight, overweight, and obesity were calculated by gender, age, and country. Prevalence and 95% confidence intervals (CI) were calculated for regional and country-level income. Results: The total prevalence of underweight, overweight and obesity among young adolescents with hunger was 6.2% (95% CI: 4.4–8.0%), 25.1% (95% CI: 20.3–29.9%) and 8.9% (95% CI: 6.5–11.3%), respectively. Southeast Asia had the highest prevalence of underweight (17.2%; 95% CI: 7.3–27.0%). America had the highest regional prevalence of obesity (11.1%; 95% CI: 7.2–15.1%) and overweight (28.9%; 95% CI: 21.9–35.9%). Low income countries had relatively high prevalence of underweight (11.5%; 95% CI: 3.2–19.9%). High income countries had the highest prevalence of obesity (17.4%; 95% CI: 14.9–19.9%) and overweight (38.7%; 95% CI: 32.0–45.4%). The co-existence of underweight and overweight among adolescents with hunger was highest in the Eastern Mediterranean region, and in upper-middle and high-income countries. Conclusions: There is a dual burden of underweight and obesity among adolescents with hunger aged 12–15 years, which differs between geographical regions. The integration of targeted interventions and policies is required to simultaneously address both underweight and increasing rates of obesity among adolescents with hunger in different regions.